Building malls or metros? South Africa's exports of tradable urban services to the rest of Africa - Ivan Turok; Justin Visagie (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2020)
Service industries are increasingly important in international trade and offer additional paths to economic development. There are many opportunities to expand trade in services between South Africa and other African countries. Improvements in urban planning, design, and governance are vital to create more productive and liveable cities. South Africa has many capabilities to support urbanization in Africa. However, South African companies have been relatively unsuccessful at exporting this expertise, and more successful at exporting retail, financial, and telecoms services. One reason is that urban infrastructure projects are discrete, risky, and costly. South African companies have tended to go it alone, with minimal commitment to host nations and little support from governments or other firms. Some have been absorbed into larger multinational corporations. There has been no concerted effort in South Africa to promote tradable urban services as a package of capabilities that could unleash greater economic dynamism within both source and host countries.
Keywords: L80; O14; O18; O55; 330; Africa; international trade; South Africa; tradable urban services; urban infrastructure; urbanization